Economic Reforms - Industry & Technical Education - Patankar, A. C. (Journal of Engineering Education Transformations, 1993)
Human Resource is a vital input to the industry. Technical institutions provide the basic training to this resource. India is fortunate to have a well developed system of technical education which is imparted through industrial training institutes, polytechnics, degree colleges and higher institutes of technology.